Comparative Nutrigenomics Analysis of the Pig, Mouse and Human (P15-004-19). (13th June 2019) - Dawson, Harry; Chen, Celine; Wang, Thomas; Urban, Joseph
Abstract: Objectives: The seminal work of Miller and Ullrey examined the suitability of the pig as a model for human nutrition concluded "With the possible exception of nonhuman primates, it is apparent that the omnivorous pig is one of the best models for study of nutrition issues in the omnivorous human." To date, a cross-species, large-scale analysis of genes related to nutrition and metabolism has not been reported. Our goal was to systematically review similarities and differences in nutrition-related physiology, and where different, to explore possible etiologies behind each phenomena using comparative genomics. Methods: A broad literature and laboratory-based analysis was conducted comparing 1532 genes associated with porcine, murine, and human macro and micronutrient metabolism, including metalloproteins. Four questions were addressed. Are genes in specific pathways conserved? Are the genes/proteins structurally and functionally similar? Are the genes expressed in similar cell types? Are the genes regulated in a similar manner to stimuli? Results: Pigs have roughly 4-fold fewer unique genes (66) than the mouse (240) and human (209). The great majority of these unique genes were zinc-containing members of the KRAB-A box Transcription Factor Superfamily. Analysis of 142 non-orthologous genes revealed that these genes were 10 times more likely to be present in only pigs and humans (120) than only in mice and humans (17). Genes involved in vitamin A and lipid metabolism were more highly conserved between pigs and humans. Notable, differences were found between humans and pigs in regard to genes encoding digestive enzymes and nutrient sensing genes. In some cases, mechanistic data were obtained to explain for previously described differences in physiology. For example, the lack of porcine salivary lipase and amylase activities is likely related to the absence of these genes in the pig. Analysis of 888 orthologous genes indicated a greater pig-human protein similarity for almost every gene examined. Conclusions: Overall, the genomic and physiological parameters examined were more similar between pigs and humans than mice and humans. This supports the proposition that evaluating nutrition in pigs provides data that is more physiologically relevant to humans. Funding Sources: Supported by USDA/ARS Project Plan 1235-51, 000-055-00D.